2005
DOI: 10.1007/s10346-005-0016-x
|View full text |Cite
|
Sign up to set email alerts
|

A statistical approach to landslide risk modelling at basin scale: from landslide susceptibility to quantitative risk assessment

Abstract: A procedure for landslide risk assessment is presented. The underlying hypothesis is that statistical relationships between past landslide occurrences and conditioning variables can be used to develop landslide susceptibility, hazard and risk models. The latter require also data on past damages. Landslides occurred during the last 50 years and subsequent damages were analysed. Landslide susceptibility models were obtained by means of Spatial Data Analysis techniques and independently validated. Scenarios defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(80 citation statements)
references
References 12 publications
0
67
0
4
Order By: Relevance
“…As the hydraulic conductivity based on field measurements was not available for the study area, this parameter was estimated for the identified soil types based on the work developed by Rawls et al (1982), which summarized the typical hydraulic conductivities for different soil types starting from the respective textural properties. The national digital soil map at 1 : 25 000 scale (DGADR, 1999) was used to extract the clay, silt and sand, and coarse sand fractions for the different soils types in the study area.…”
Section: Hydraulic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…As the hydraulic conductivity based on field measurements was not available for the study area, this parameter was estimated for the identified soil types based on the work developed by Rawls et al (1982), which summarized the typical hydraulic conductivities for different soil types starting from the respective textural properties. The national digital soil map at 1 : 25 000 scale (DGADR, 1999) was used to extract the clay, silt and sand, and coarse sand fractions for the different soils types in the study area.…”
Section: Hydraulic Modelmentioning
confidence: 99%
“…Guzzetti et al, 2005;Remondo et al, 2005). The relevance for using this study area limits when assessing rainfall-triggered landslide susceptibility is related with the maintenance of the hydrologic processes continuity, mainly runoff and potential infiltration.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of quantitative risk analysis (QRA) at regional scale can be found in Cardinali et al (2002), Remondo et al (2005) and Catani et al (2005). However, these studies provide a mean annual risk with no information on the expected distribution of annual costs.…”
Section: P Nicolet Et Al: Shallow Landslide's Stochastic Risk Modelmentioning
confidence: 99%
“…The database has been the subject of a number of hazard studies (Remondo [7]; Remondo et al [8], [9]). It has been later expanded with addition of socioeconomic information to enable risk assessment (Remondo et al [6]; Bonachea [10]). It covers approximately 140 km 2 , with elevations ranging between 0 m and 700 m a.s.l., and the main annual rainfall is 1500 mm.…”
Section: Study Area Sub-areas and The Problemmentioning
confidence: 99%
“…Examples can be seen of studies of different area extensions with diverse densities of landslide occurrences (van Westen et al [2], 21 km 2 ; Zêzere et al [3], 17 km 2 ; Coe et al, [4], about 315 km 2 , or Cardinali et al [5], 79 places surrounding known landslides within a 8456 km 2 region; and Remondo et al [6], a 500 km 2 area). Generally, no particular statistical justification is used (put forward) for a study and mainly reasons of geomorphologic or physiographic uniformity, cartographic unit delimitation or sociologic relevance are the arguments used to justify the selection of study area and of its boundaries.…”
Section: Introductionmentioning
confidence: 99%